Experimental study on fire resistance of cold-formed steel built-up box columns. (February 2020) - Yang, Jingjie; Wang, Weiyong; Shi, Yu; Xu, Lei
Abstract: Cold-formed steel built-up box columns are commonly used in mid-rise cold-formed steel buildings to resist applied loads. Numerous studies have been conducted to evaluate the load-bearing capacity of the columns at ambient temperature but there is very limited research on the fire resistance of the built-up columns. In this paper, a full-scale experimental investigation on fire responses of sixteen axially loaded cold-formed steel built-up box columns was conducted. As a benchmark, the load-bearing capacity of the columns at ambient temperature was tested first. The effects of heating rate, load ratio, and temperature distribution pattern on the fire responses of the columns were investigated in the fire tests. The test results indicated that increasing the load ratio led to a significant decrease in the member critical temperatures, which consequently reduced the fire resistance of the columns considerably. For those columns with an applied load ratio lower than 0.6, they were expected to have member critical temperatures higher than 500 °C. Moreover, with thin-walled steel and no fire protection the column temperatures increased quickly, leading to failure in no more than 12 min in a fast fire even with a low load ratio. It was also found that creep deformation associated with the low heating rate was one of the important factors that could be detrimental to the fire resistance and member critical temperature. As for the effect of temperature distribution patterns in the columns on the member critical temperature, it was found that the member critical temperatures for specimens with non-uniform temperature distribution were slightly higher than those with uniform temperature distribution. Highlights: Full-scale tests on cold-formed steel built-up box columns were presented. The tests contain two load-bearing capacity tests and sixteen fire-resistance tests. Effects of Load ratio, heating rate and temperature distribution patterns were investigated in the tests.